Legal Implications of Insurance Supervisor's Liability in Policy Failure - Soca Daru Indraswari (Perantara Law Review, 2024)
The ambiguity of the norms in Article 15 of Insurance Law Number 40 of 2014 has led to multiple interpretations in practice, especially in relation to the scope of the responsibility of the controller of an insurance company in the case of policyholder default. This study aims to analyze the limits of the responsibility of the controller of an insurance company for the default of policyholders by referring to the case of PT Asuransi Jiwasraya in case 676/PDT/2021/PT DKI. This research uses a normative legal method with a statutory approach, conceptual approach, and case approach, and is analyzed using grammatical and systematic interpretation. The results show that there is legal uncertainty in the regulation of the responsibility of the controller of the insurance company, which has an impact on legal protection for policyholders. This finding confirms the need for more explicit regulations regarding the scope of controlling liability in order to provide legal certainty and more optimal protection for policyholders. Therefore, the recommendations include the need for revision of related regulations as well as strengthening the supervision mechanism of insurance company controllers.